(E-Taste Apps) – visualization food taste descriptors - Abd Latif, Noor Syazwani (2019)
Malaysia is multiracial countries which have variety cultures, customs, tradition and have their own local food which is part of gastronomic products. The problem faced by the tourist or foreigners are they do not really familiar with Malaysian food. They do not know what taste that the food contains. Some of them do not prefer spicy, sweet or sour too much in the food. So, they faced the problem in finding the food that they prefer the taste. Therefore, this project is the way to assist the foreigners or tourist to identify the taste of the food by using the mobile application technology. The objectives of this project are to identify the user requirements of E-Taste mobile application for the foreigners, design and develop E-Taste mobile application content based on user requirement. The scope of this project is foreigner or tourists that come to Malaysia. This project used the Design Thinking as the methodology approach to the development of E-Taste mobile application. Design thinking process is divided into five stages which comprises of empathizing, define, ideate, prototype, and test. Based on the result from user testing, it shows a positive feedback from the foreigners or tourists. As conclusion, E-Taste mobile application may assist the foreigners or tourists by view the graph visualization of the food taste.